2020
DOI: 10.3390/ma13163614
|View full text |Cite
|
Sign up to set email alerts
|

Application of Texture and Fractal Dimension Analysis to Estimate Effectiveness of Oral Leukoplakia Treatment Using an Er:YAG Laser—A Prospective Study

Abstract: Background: Oral leukoplakia (OL) is a potential neoplasmic lesion. The aim of this study was to apply texture analysis (TA) and fractal dimension analysis (FDA) to estimate the effectiveness of OL treatment using an Er:YAG laser. Methods: Eighteen patients with 32 lesions were treated. Laser procedures were conducted using the LiteTouch™ Er:YAG Dental Laser. The diameter of the operational tip was 1.3 mm, the power was 50 mJ, the frequency was 50 Hz, and the wavelength was 2940 nm. TA was based on long and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…In this work, it was reported that the FD values increased as the age of the patients increased. Along the same lines, Jurczyszyne et al [ 37 ] reported that in OL patients treated with a LiteTouch™ Er: YAG dental laser, the FD in the photographic images increased significantly after laser treatment, allowing FD to be used as a control mechanism for the effectiveness of the treatment.…”
Section: Discussionmentioning
confidence: 91%
“…In this work, it was reported that the FD values increased as the age of the patients increased. Along the same lines, Jurczyszyne et al [ 37 ] reported that in OL patients treated with a LiteTouch™ Er: YAG dental laser, the FD in the photographic images increased significantly after laser treatment, allowing FD to be used as a control mechanism for the effectiveness of the treatment.…”
Section: Discussionmentioning
confidence: 91%
“…Converting a colour image to a single-bit image is a process in which some of the analysed details are lost. We showed that the FD of oral leukoplakia was significantly lower than that of healthy mucosa with no statistical differences between the treated lesion and healthy mucosa [ 36 ]. In the aforementioned study, the FD of the examined lesion was lower than that of the reference mucosa, and after treatment, it was close to that of the normal mucosa, as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Although the present review focused on the diagnostic and prognostic value of fractal analysis in oral oncology, the literature reported some sporadic and preliminary works dealing with the monitoring of treatments as reported by the Polish group of Jurczyszyn et al [51,52], who applied fractal dimension and texture analysis of lesion autofluorescence in the evaluation of oral lichen planus treatment effectiveness and in estimating the effectiveness of oral leukoplakia treatment using the LiteTouch™ Er:YAG Dental laser, or by Varsha et al, who recently explored the pre-and post-treatment objective evaluation of remission in oral lichen planus using fractal analysis and compared it with the visual analog (VAS) scale [53].…”
Section: Future Directionsmentioning
confidence: 99%